Dampak Peremajaan (Replanting) Kelapa Sawit Terhadap Kondisi Ekonomi Petani Plasma Di Desa Bukit Jaya Kecamatan Sungai Lilin Kabupaten Musi Banyuasin - Mulyani Mulyani; Zainuddin Zainuddin; Bayu Setiawan (Universitas Batangahari Jambi, 2023)
This study aims to describe the stages of implementing oil palm rejuvenation by plasma farmers and analyze the economic impact on plasma farmers during the replanting period in Bukit Jaya Village, Sungai Lilin District, Musi Banyuasin Regency. As for this study, data analysis using the Wilcoxon Match Pairs Test data, according to Sugiyono (2017), this technique is a refinement of the sign test, if in the sign test the magnitude of the difference in the number values between positive and negative is not taken into account, whereas in the Wilcoxon test this counts. As in the sign test, this technique is used to test the comparative hypotension significance of two correlated samples when the data are ordinal. The results showed that the Wilcoxon signed ranks test obtained an asymp.sig (2-tailed) value of 0.000. Because the value of 0.000 is less than 0.05, H0 is rejected and Ha is accepted, which means that there is an average difference between pest-test and post-test income. So that it can be said that there was a decrease in the income of plasma farmers in Bukit Jaya Village, Sungai LiLin District, Musi Banyuasin Regency before and during the rejuvenation period